THE INFLUENCE OF BRAND IMAGE, PAYMENT SYSTEM, AND PROMOTION ON INTEREST IN COLLEGE AT THE UNIVERSITAS MAHKOTA TRICOM UNGGUL - Haryani, Dwi Septi; Nasib; Zahra, Aminatu (International Journal of Accounting, Management, Economics and Social Sciences (IJAMESC), 2023)
This study aims to find out whether brand image, payment systems and promotions affect a person's interest in continuing their studies at Mahkota Tricom Unggul University. The method used in this study uses quantitative methods. Furthermore, the data collection technique uses a questionnaire. The data analysis technique uses multiple linear regression analysis with the help of IBM SPSS Software. The results of the study show that (1) Brand Image influences interest in studies at the University of Mahkota Tricom Unggul Medan. (2) The payment system affects interest studies at the University of Mahkota Tricom Unggul Medan. (3) The promotion affects my interest in studying at the University of Mahkota Tricom Unggul. (4) Brand image, payment system, and promotion simultaneously affect the exciting study at the University of Mahkota Tricom Unggul Medan.